The lichen genus Cetrelia (Parmeliaceae, Ascomycota) in india - Mishra, Gaurav Kumar (Phytotaxa, 2015)
A detailed morpho-taxonomic account of ten species of the lichen genus Cetrelia occurring in India is provided. Cetrelia chicitae (W.L. Culb.) W.L. Culb. & C.F. Culb., is reported as new to India. A key to all worldwide known taxa of Cetrelia is provided.